Decision Criteria for Selecting an Eye Care Professional in South Africa - Faul, Garrick Stewart (My University, 2012)
Optometry comprises of a professional service coupled with a retail product administered through third party medical aid payments, all adding to the complexity regarding the patient’s perception to the industry. There is inadequate knowledge of consumers’ needs, in addition to a culture of individualism amongst the practitioners, causing inefficient competitiveness. More research, with a network of free-flowing information, can facilitate the necessary change to understand how consumers make decisions regarding their optometrist. Important attributes have been identified through a review of available literature and past research. These attributes were categorised by three levels, allowing a research instrument to be developed using Saw Tooth Software. A conjoint analysis was done from the data collected by the survey, resulting in the relevant importance of the decision criteria. Furthermore, T-tests and ANOVA tests were performed on the demographic groups, establishing any significant differences. Of the four attributes, Selection and the Optometrist were found to be the most important relative to the others, particularly regarding a wide product choice and word-of-mouth referrals. The T-tests and ANOVA tests found few significant differences, indicating all people see optometry as a global need. However, future research is required to identify more specific segments relative to the optometric market thereby enabling a better understanding of their needs. Although the research has resulted in practical information, it has highlighted the desperate need of many South Africans who do not have access to eye care. A definite gap exists between those who have adequate eye care and those without. It is hoped that future research will explore the inequalities in the eye care industry, providing valuable answers so that all South Africans have adequate access to eye care
MBA thesis (WBS)
Keywords: Eye care; Optometrists